The Translation of Sex-Related Language: The Danger(s) of Self-Censorship(s) - Santaemilia, José (TTR, 2008)
AbstractWhile censorship is an external constraint on what we can publish or (re)write, self-censorship is an individual ethical struggle between self and context. In all historical circumstances, translators tend to produce rewritings which are ‘acceptable’ from both social and personal perspectives. The translation of swearwords and sex-related language is a case in point, which very often depends on historical and political circumstances, and is also an area of personal struggle, of ethical/moral dissent, of religious/ideological controversies. In this paper we analyse the translation of the lexeme fuck into Spanish and Catalan. We have chosen two novels by Helen Fielding—Bridget Jones’s Diary (1996) and Bridget Jones: The Edge of Reason (1999)—and the translations into the languages mentioned. Fielding’s acclaimed first novel has given rise to a distinctive genre of popular fiction (chick lit), which is mainly addressed to young cosmopolitan women and deals unconventionally with love and sex(uality). Historically, sex-related language has been a highly sensitive area; if today, in Western countries at least, we cannot defend any form of public censorship, what we cannot prevent (nor probably should we) is a certain degree of self-censorship, along the lines of an individual ethics and attitude towards religion, sex(uality), notions of (im)politeness or (in)decency, etc. Translating is always a struggle to reach a compromise between one’s ethics and society’s multiple constraints—and nowhere can we see this more clearly than in the rewriting(s) of sex-related language.